2001
DOI: 10.1046/j.1444-2906.2001.00265.x
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of pectenotoxin-2 to pectenotoxin-2 seco acid in the New Zealand scallop, Pecten novaezelandiae

Abstract: SUMMARY: Comparison of pectenotoxin (PTX) profiles between the toxic dinoflagellate Dinophysis acuta and scallops Pecten novaezelandiae collected at Wedge Point, Queen Charlotte Sound, New Zealand was carried out by liquid chromatography–mass spectrometry (LC‐MS) with turbo‐ionspray ionization. Although the major PTX homolog in D. acuta was pectenotoxin‐2 (PTX2), the scallops contained pectenotoxin‐2 seco acid (PTX2SA) as the predominant toxin. Pectenotoxin‐2 isolated from D. acuta was rapidly converted to PTX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 18 publications
0
32
0
1
Order By: Relevance
“…However, there have been documented reductions in cockle beds which were correlated with salinity reduction following freshwater input from a hydroelectric power station in Doubtful Sound, South Island (Tallis et al 2004). Some authors also suggest that eutrophication, red tides and toxic algal blooms provide an increasing threat to bivalve populations, including scallops, mussels and clams, in New Zealand (Marsden 1993;Mackenzie et al 1996;Rhodes et al 2001;Suzuki et al 2001;Grant and Hay 2003).…”
Section: Introductionmentioning
confidence: 93%
“…However, there have been documented reductions in cockle beds which were correlated with salinity reduction following freshwater input from a hydroelectric power station in Doubtful Sound, South Island (Tallis et al 2004). Some authors also suggest that eutrophication, red tides and toxic algal blooms provide an increasing threat to bivalve populations, including scallops, mussels and clams, in New Zealand (Marsden 1993;Mackenzie et al 1996;Rhodes et al 2001;Suzuki et al 2001;Grant and Hay 2003).…”
Section: Introductionmentioning
confidence: 93%
“…1), pectenotoxin-3 (PTX-3) (C-43 = aldehyde) and pectenotoxin-6 (PTX-6) (C-43 = carboxylic acid) in the digestive gland of P. yessoensis [7]. However, PTX-2 is rapidly metabolized to pectenotoxin-2 seco acid (PTX-2SA) in most bivalve species throughout the world, including New Zealand [8,9], Norway [10] and Portugal [11]. Structurally, PTX-2SA is identical to PTX-2 except that the characteristic lactone ring is hydrolyzed in the seco acid form (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that many of the other PTXs such as PTX6 and PTX2 seco acid (PTX2sa) 54 are formed by metabolism of PTX2 in shellfish tissues. 38,[55][56][57] Several analytical methods for the determination of PTXs by LC-MS or LC-MS/MS are reported. + are applicable to quantification of the PTXs.…”
Section: 3mentioning
confidence: 99%